ANALYSIS OF PRINCIPLE DIMENSION AND SHAPE OF PURSE SEINERS IN AMBON ISLAND - Helly S Lainsamputty (ALE Proceeding, 2019)
Abstrak Purse seiners as a ship's main small pelagic fish Catcher is increasingly growing in number and size. In the last 5 years has been an increase in purse seine boats in Maluku by 20% and 15% of the overall operating in waters around the island of Ambon. Purse seiners tend to be made traditionally based on experience and not in accordance with the criteria of size comparison of a fish boat. It is very technical and operational feasibility of affect in this speed, stability and longitudinal strength . This research aims to calculate speed, tonnage (GT), the size of the principal as well as set the geometric shapes of purse seiners on the island of Ambon. The methods used in this research is a survey method by gathering primary and secondary data by making observations and measurements directly against the 32 purse seiners in Ambon island. Analysis and discussion is done through estimation the ship's speed by using the formula of Nomura, estimated tonnage (GT) using the Standard Fish Vessel Regulations by the Director-General of Fisheries Catch of Indonesia in 2004, the determination of the optimal size of the principal ship in the empirical formula by numerical – Traung and geometric forms of purse seiner . Estimation against speed (V) and the tonnage (GT) shows that the speed average (Vaverage) = 7.1 knots and tonnage average(GTaverage) = 22.4 tons. The calculation of the size of the principal ship by using empirical methods-numerical based on Traung equation with input of Vaverage and GTaverageindicates that the principal dimension is as follows: LBP = 15.8 meters; B = 4.8 meters; D = 2.2 meters and d = 1.9 meters and form coefficient as follows : CB = 0,6 ; CW = 0,7 ; CM = 0,97 ; CP = 0,62